Synthesis, Characterization and in vitro Cytotoxicity Studies of Pentadentate Ligand and its Copper(II) Complexes - Chokkanathan, Umapathy; Geetha, Kannappan (Asian Journal of Chemistry, 2017)
A pentadentate ligand was synthesized by reaction of 4-t-butyl-2,6-bis(chloromethyl)phenol and isonicotinic hydrazide. The ligand was characterized by UV-visible, FT-IR, 1H NMR, 13C NMR and mass spectrascopic techniques. The above ligand was coordinated with various copper precursors to form corresponding copper(II) complexes. The complexes were characterized by UV-visible, FT-IR, molar conductivity and cyclic voltammetry. The in vitro cytotoxicity of the ligand and its copper complexes were studied against Ehrlich ascites carcinoma (EAC) cells.